Investigation of antidiarrheal and hypoglycemic activities of clerodendrum viscosum root extract in mice - Saara, Sadia Masood (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017